Karakteristik Pemilihan Venue Pameran oleh Perusahaan Penyelenggara Pameran di Jakarta - Fauzi Mubarak; Rimsky K. Judisseno; Heri Setyawan (Bisnis Event, 2026)
This study aims to identify the factors influencing Professional Exhibition Organizers (PEOs) in selecting exhibition venues in Jakarta. As Indonesia’s economic hub, Jakarta provides several large-scale facilities such as the Jakarta Convention Center (JCC), Indonesia Convention Exhibition (ICE) BSD, and Jakarta International Expo (JIExpo) Kemayoran. The study employs a quantitative-descriptive approach through a survey of 120 active PEOs and in-depth interviews with key venue managers. Data were analyzed using descriptive statistics, Pearson correlation, and Exploratory Factor Analysis (EFA). The results show five main factors affecting venue selection: (1) accessibility and transport, (2) facilities and flexibility, (3) service and professionalism, (4) image and reputation, and (5) pricing and administrative convenience. ICE BSD and JCC are the most preferred venues for their reliability and reputation. The findings conclude that venue selection decisions are driven more by experiential value and operational efficiency rather than rental cost. The study recommends the development of a digital platform, “Jakarta MICE Venue Hub”, to enhance collaboration and competitiveness of Jakarta’s MICE industry.